Metabarcoding detection of Vibrio species in black-tailed gulls reveals seabirds as overlooked sentinels of coastal zoonotic risk in South Korea - Singeun Oh; Dewi Arinta; Buyanbadrakh Burenbaatar; Jun Ho Choi; Leon Kim; Du-Yeol Choi; Dongjun Kang; Arwa Shatta; Myung-hee Yi; Yoon Hee Cho; In-Yong Lee; Ju Yeong Kim (Environmental Research, 2026)

Hydrogen production via direct core-shell conjugation of functionalized fullerenes and ZnO QDs with accelerated optical catalytic properties - Juhee You; Dan Na; Yuwen Wei; Hyunjin Cho; Seok-Ho Seo; Young Jae Park; Dong Gwon Heo; Sang-Youp Yim; Seunghwan Kim; Soohyung Park; In Seok Seo; Mehmet Suha Yazici; et al. (Chemical Engineering Journal, 2026)

Dielectric oligonucleotide fragments enable ultralow threshold photomultiplication in infrared quantum dot photodetectors - Yongnam Ahn; Jinwoo Shin; Woo Hyuk Jung; Yong Ho Cho; Minjung Yang; In-Suh Lee; Jaewoo Jeong; Taeho Han; Seoryeon Jeong; Jin Ah Lee; Chae Hyeong Ha; Yoon Jang Chung; et al. (Chemical Engineering Journal, 2026)

The impact of redox changes on uranium migration using a field tracer test and reactive transport modeling - In-Hee Cho; Suh-Ho Lee; In-Woo Park; Jaeyeon Kim; Won-Tak Joun; Kang-Kun Lee (Journal of Hazardous Materials, 2026)

Trait–environment diagnosis of ecological instability in Korean streams using benthic diatoms and machine learning: a UMAP–CDI framework - Jun-Ho Lee; Hyo Gyeom Kim; Byeong-Hun Han; In-Hwan Cho; Ha-Kyung Kim; Eun-A. Hwang; Su-Ok Hwang; Baik-Ho Kim (Aquatic Sciences, 2026)

Near-infrared light–responsive implantable module integrated into glaucoma drainage device for controlled antifibrotic drug therapy - Chang Hee Min; Young In Shin; Han Bi Ji; Soo Bin Yoon; Yeonseo Kim; Cho Rim Kim; Jae Hoon Han; Min Ji Kim; Myung Ju Kim; Eun Jung Kwon; Young Kook Kim; Ki Ho Park; et al. (Chemical Engineering Journal, 2026)

Development of granular road assessment and asset management tool for quantifying superload impacts - Nazmus Sakib Ahmed; Yongsung Koh; Nazik Citir; Halil Ceylan; Sunghwan Kim; In Ho Cho (Transportation Geotechnics, 2026)

Pollution characteristics of PM2.5 and PM1.0 at urban and background sites in South Korea: Focusing on health risks of PAHs and heavy metals - Sang-Jin Lee; Ho-Young Lee; In-Gyu Cho; Seong-Joon Kim; Ji Yi Lee; Hye-Jung Shin; Young Sung Ghim; Yong Pyo Kim; Sung-Deuk Choi (Atmospheric Environment, 2026)

Future variability in groundwater-surface water interactions: Implications for streamflow and its components using SWAT-MODFLOW 6 and CMIP 6 projections - Suh-Ho Lee; Hye-Ji Kim; In-Hee Cho; Seong-Sun Lee; Hyemin Park; Youn-Tae Kim; MoonSu Kim; Kang-Kun Lee (Journal of Hydrology, 2026)

Enhancing CO2-to-CH4 conversion efficiency of TiO2 through synergistic morphology tuning, defect engineering, and heterojunction formation - Dongyun Kim; Kyuseok Lee; Young Ho Park; Junho Lee; Jeonghyeon Lee; Chaelin Shin; Hyeonjong Jeong; Chang-Hee Cho; G. Murali; Seung Jun Lee; Insik In; Su-Il In (Chemical Engineering Journal, 2026)

Enhanced remediation of radioactive soil via synergistic foam flotation-acid washing process in a single reactor - Gayeon Kim; Hajin Baek; Sangyoon Kim; In-Ho Yoon; Kyung Hwa Cho; Ilgook Kim (Journal of Environmental Chemical Engineering, 2025)

Explainable AI-based evaluation of factors affecting heavy metal removal by microalgae-based adsorbents - Gyu-Ri Choi; Heejin Yang; Jong Ho Lee; Tan Runfa; In Sun Cho; Seong-Jik Park; Chang-Gu Lee; Jin-Kyu Kang (Journal of Applied Phycology, 2025)

ELF18-INDUCED LONG NONCODING RNA 25 positively regulates the pathogen defense-related CYP82C2 expression in Arabidopsis - Jun Sung Seo; Moon-Joo Lee; Jimin Lee; Nuri Oh; So-Young Jang; Ye In Cho; Jin-Ho Kang; Jang-Kyun Seo; Hye Sun Cho; Moonhyuk Kwon; Choonkyun Jung (Journal of Plant Biology, 2025)
Long noncoding RNAs (lncRNAs) are emerging as important regulators of gene expression during plant immune responses. In this study, we identified a novel lncRNA, ELF18-INDUCED LONG NONCODING RNA 25 ( ELENA25 ), located in the intergenic region between AT4G31960 and CYTOCHROME P450, family 82, subfamily C, polypeptide 2 ( CYP82C2 ) in Arabidopsis. ELENA25 was initially identified through custom lncRNA microarray data. Here, its full-length sequence (810 bp) was determined using primer walking and confirmed by sequencing. ELENA25 expression was preferentially induced by flg22, a bacterial pathogen-associated molecular pattern (PAMP), in a late-phase and FLS2 receptor-dependent manner. Neighboring genes AT4G31960 and CYP82C2 were also flg22-inducible, with expression abolished in the fls2 mutant background. To assess whether ELENA25 regulates the expression of nearby genes, we generated ELENA25 -overexpressing (OX) and knockout (KO) plants. In ELENA25 OX lines, CYP82C2 expression was significantly upregulated under normal and flg22-treated conditions, while AT4G31960 expression remained unchanged. Conversely, in the elena25 mutants (KO), CYP82C2 expression was significantly reduced, indicating that ELENA25 positively regulates CYP82C2 transcription. Expression levels of other nearby cytochrome P450 genes, including CYP82C3 and CYP82C4 , and other indole glucosinolate-related CYP genes were not affected by ELENA25 expression changes. Collectively, our results demonstrate that ELENA25 is a flg22-inducible lncRNA that specifically enhances CYP82C2 expression in a FLS2-dependent manner. This study provides new insights into the role of lncRNAs in plant innate immunity, highlighting ELENA25 as a positive regulator of defense-related gene expression.

Multi-Enzyme Supplementation to Diets Containing 2 Protein Levels Affects Intramuscular Fat Content in Muscle and Modulates Cecal Microflora Without Affecting the Growth Performance of Finishing Pigs - Qianqian Zhang; Sungbo Cho; Junho Song; Jinuk Jeong; Minjae Yu; Seyoung Mun; Kyudong Han; In Ho Kim (Probiotics and Antimicrobial Proteins, 2025)

Defect-engineered black indium oxide: A high-performance photothermal material for solar-driven water purification - Runfa Tan; Tatachari Santhanagopalan Shridharan; Jong Ho Lee; Mukkath Joseph Josline; Jae Yeong Lee; Jong Seong Bae; Arumugam Sivanantham; Yoo Jae Jeong; Jae-Hyun Lee; Sangwook Lee; In Sun Cho (Desalination, 2025)

Fish oil a source of omega-3 fatty acids affects hypothalamus heat resistance genes expressions and fatty acid composition in heat-stressed chicks - Hatem M. El-Tahan; Chun Ik Lim; Ahmad R. Alhimaidi; Aiman A. Ammari; Sungbo Cho; In Ho Kim; Hossam M. El-Tahan (Domestic Animal Endocrinology, 2025)

Monitoring of organochlorine pesticides using pine needle, pine bark, and soil samples across South Korea: Source apportionment and implications for atmospheric transport - Sanjenbam Nirmala Khuman; Ho-Young Lee; In-Gyu Cho; David Chung; Soo Yong Lee; Jangho Lee; Jung-Keun Oh; Sung-Deuk Choi (Chemosphere, 2025)

Applicability of plant–clay mineral composite for rapid algae removal from eutrophic freshwaters at the laboratory and field scales - Byeong-Hun Han; Hyo Gyeom Kim; Young-Hyo Kim; In-Hwan Cho; Ha-Kyung Kim; Sungwon Hong; Baik-Ho Kim (Environmental Research, 2025)

Development of a comprehensive air risk index and its application to high spatial-temporal health risk assessment in a large industrial city - Sang-Jin Lee; In-Gyu Cho; Ho-Young Lee; Jeong-Tae Ju; Hye-Jung Shin; Sung-Deuk Choi (Environmental Pollution, 2025)

Chitosan-gallic acid conjugate edible coating film for perishable fruits - Cho Rok Lee; Su Jin Lee; Tae In Kim; Kiramage Chathuranga; Jong Soo Lee; Sangsik Kim; Min Hee Kim; Won Ho Park (Food Chemistry, 2025)

Simple synthesis of K/P co-doped graphitic carbon nitride to enhance photocatalytic performance under simulated solar irradiation - Jong-Min Lee; Youn-Jun Lee; Jong Ho Lee; Runfa Tan; Jin-Sil Kim; In Sun Cho; Seong-Jik Park; Chang-Gu Lee (Environmental Research, 2025)

UV photoreduction-driven heterogeneous fenton-like process: Long-term reactivation of fenton sludge-derived biochar and enhanced acetaminophen degradation - Heejin Yang; Sung-Hyo Jung; Jong Ho Lee; In Sun Cho; Seong-Jik Park; Chang-Gu Lee (Journal of Water Process Engineering, 2024)

Distribution coefficient prediction using multimodal machine learning based on soil adsorption factors, XRF, and XRD spectrum data - Seongyeon Na; Heewon Jeong; Ilgook Kim; Seok Min Hong; Jaegyu Shim; In-Ho Yoon; Kyung Hwa Cho (Journal of Hazardous Materials, 2024)

Polyhexamethylene guanidine phosphate induces pyroptosis via reactive oxygen species-regulated mitochondrial dysfunction in bronchial epithelial cells - Jun Young Park; Ji-Hee Kim; Chan Ho Park; Sung-Hwan Kim; In-Hyeon Kim; Won Gil Cho (Toxicology, 2024)

Sex, age, and species differences of perfluorooctanoic acid modeled by flow- versus permeability-limited physiologically-based pharmacokinetic models - Go-Wun Choi; Dong Wook Kang; Ju Hee Kim; Seok-jin Cho; Yong-Bok Lee; In-Ho Kwon; Hea-Young Cho (Toxicology, 2024)

Insights and machine learning predictions of harmful algal bloom in the East China Sea and Yellow Sea - Jiyi Jang; Sang-Soo Baek; Daehyun Kang; Yongeun Park; Mayzonee Ligaray; Seung Ho Baek; Jin Yong Choi; Bum Soo Park; Myong-In Lee; Kyung Hwa Cho (Journal of Cleaner Production, 2024)

Unique photothermal material: Copper phosphate (Cu3P2O8) with broadband visible-to-near-infrared absorption properties for efficient solar steam generation - Tatachari Santhanagopalan Shridharan; Jong Ho Lee; Runfa Tan; Arumugam Sivanantham; Hyun Soo Han; Hyun Suk Jung; In Sun Cho (Desalination, 2024)

Have climate change and warmer winters altered freeze-thaw patterns? - Masrur Mahedi; Daniel Rajewski; Halil Ceylan; Sunghwan Kim; Eugene S. Takle; In-Ho Cho (Transportation Geotechnics, 2024)

Mechanochemical activation of silicon photothermal material for efficient interfacial solar desalination and wastewater purification - Tatachari Santhanagopalan Shridharan; Arumugam Sivanantham; Jong Ho Lee; Seo Yeong Hong; Yoo Jae Jeong; Seong Sik Shin; In Sun Cho (Chemical Engineering Journal, 2024)

Predicting the distribution coefficient of cesium in solid phase groups using machine learning - Seok Min Hong; In-Ho Yoon; Kyung Hwa Cho (Chemosphere, 2024)

Optimizing electroactive membrane performance for microalgae harvesting: A response surface methodology study of membrane formulation and operating parameters for electro filtration - Azeem Mushtaq; Hoon Cho; Asma Batool; Muhammad Tahir Fazal; Muhammad Aslam; Muhammad Saif UR. Rehman; Jason Chun-Ho Lam; Jong-In Han (Chemosphere, 2024)

Production and separation of 2,5-furandicarboxylic acid in gamma-valerolactone solvent system using glucaric acid as raw material derived from oxidation of enzymatic hydrolysate of Miscanthus sacchariflorus - Jonghwa Kim; Jong-Chan Kim; Young-Min Cho; Chae-Hwi Yoon; Hyo Won Kwak; June-Ho Choi; Hoyong Kim; In-Gyu Choi (Biomass and Bioenergy, 2024)

First report of cycas necrotic stunt virus in a hybrid peony in South Korea - Ju-Yeon Yoon; Chandara Soeng; Ho-Jong Ju; In-Sook Cho; Bong Nam Chung (Journal of Plant Pathology, 2024)

Ecological impacts of dam construction on epilithic diatom communities in estuaries: A case study of the Korean peninsula - Ha-Kyung Kim; In-Hwan Cho; Eun-A Hwang; Young-Hyo Kim; Jeong-Suk Moon; Bae-Kyung Park; Baik-Ho Kim (Ocean & Coastal Management, 2024)

Facile and rapid fabrication of wearable biosensors via femtosecond laser-directed micro-patterning with large-sized reduced graphene oxide for physiological monitoring - Hae-In Moon; Sungil Kim; Jeong Eun Byun; Young Won Kim; Yeon Wook Jung; Seung Geun Jo; Yujin Shin; Yeoul Kang; Sang Jun Kim; Eun-Su Lee; Hyung-Jong Lee; Min-Cheol Oh; et al. (Chemical Engineering Journal, 2024)

Development of high-performance organic photodetectors by understanding origin of dark current density with synthesis of photoconductive polymers - WonJo Jeong; Jinhyeon Kang; Dongchan Lee; Cheol Shin; Hyungju Ahn; Chan So; Jong Ho Won; Dae Sung Chung; Shinuk Cho; In Hwan Jung (Chemical Engineering Journal, 2023)

Mechanisms of interactions in pattern-recognition of common glycostructures across pectin-derived heteropolysaccharides by Toll-like receptor 4 - Gyu Hwan Hyun; In Ho Cho; Yoon Young Yang; Da-Hye Jeong; Yun Pyo Kang; You-Sun Kim; Seul Ji Lee; Sung Won Kwon (Carbohydrate Polymers, 2023)

Biochemical responses and phytoremediation potential of Azolla imbricata (Roxb.) Nakai in water and nutrient media exposed to waste metal cutting fluid along with temperature and humidity stress - Sivakumar Subpiramaniyam; Sung-Chul Hong; Pyong-In Yi; Seong-Ho Jang; Jeong-Min Suh; Eun-Sang Jung; Je-Sung Park; Velmurugan Palanivel; Young-Chae Song; Lae-Hyeon Cho; Young-Hoon Park; Ji-Suk Kim (Journal of Hazardous Materials, 2023)

Bacterial Communities Associated with the Rhizosphere of Transgenic Chrysanthemum - In Soon Pack; Jin Ho Heo; Do Young Kim; Ho Jin Cho; Sung-Dug Oh; Seong-Kon Lee; Eun-Jung Suh; Chang-Gi Kim (Journal of Plant Biology, 2023)

Modeling for the estimating the adsorption property of fruit waste-based biosorbents for the removal of organic micropollutants - Bo-Gyeon Cho; Jae-Ho Lee; Hye-In Kim; Se-Been Mun; Se-Ra Jin; Dae Geun Kim; Chul-Woong Cho; Yeoung-Sang Yun (Environmental Research, 2023)

Lactucin induces apoptosis through reactive oxygen species-mediated BCL-2 and CFLARL downregulation in Caki-1 cells - Ji Hoon Jang; Cho-Young Park; Eon-Gi Sung; In-Hwan Song; Joo-Young Kim; Chuleui Jung; Ho-Yong Sohn; Tae-Jin Lee (Genes & Genomics, 2021)

Orphan nuclear receptor ERRγ regulates hepatic TGF-β2 expression and fibrogenic response in CCl4-induced acute liver injury - Yoon Seok Jung; Yong-Hoon Kim; Kamalakannan Radhakrishnan; Jina Kim; In-Kyu Lee; Sung Jin Cho; Don-Kyu Kim; Steven Dooley; Chul-Ho Lee; Hueng-Sik Choi (Archives of Toxicology, 2021)

Rapid detection of plum pox virus by reverse transcription recombinase polymerase amplification - Hwi-Won Jeong; Hyo-Jeong Lee; In-Sook Cho; Ho-Jong Ju; Rae-Dong Jeong (Journal of Plant Diseases and Protection, 2021)

Genetic analysis and population genetic structure of hard-shelled mussel, Mytilus coruscus Gould 1861 (Mytiloida: Mytilidae) from the coasts of South Korea based on mitochondrial cytochrome oxidase (COI) gene sequences - Chang Ho Yi; Moongeun Yoon; Ji Min Kim; Il-Hun Kim; In-Young Cho; Hye Suck An (Genes & Genomics, 2021)

Poor outcomes of early recurrent post-transplant bloodstream infection in living-donor liver transplant recipients - Si-Ho Kim; Seok Jun Mun; Jae-Hoon Ko; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Gyu-Seong Choi; Jong Man Kim; Jae-Won Joh; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

First report of tomato spotted wilt virus infecting Cirsium setidens in Korea - Seongmu Mun; Su-Yeon Hwang; Na-Kyeong Kim; In-Sook Cho; Ho-Jong Ju; Rae-Dong Jeong (Journal of Plant Pathology, 2021)

An inverse agonist of estrogen-related receptor γ regulates 2-arachidonoylglycerol synthesis by modulating diacylglycerol lipase expression in alcohol-intoxicated mice - Yoon Seok Jung; Yong-Hoon Kim; Kamalakannan Radhakrishnan; Jina kim; Don-Kyu Kim; Ji-Hyeok Lee; Hyunhee Oh; In-Kyu Lee; Wook Kim; Sung Jin Cho; Cheol Soo Choi; Steven Dooley; et al. (Archives of Toxicology, 2020)

Clinical effectiveness of oral antimicrobial therapy for acute pyelonephritis caused by extended-spectrum β-lactamase-producing Enterobacteriales - Si-Ho Kim; Kyoung Ree Lim; Hyunju Lee; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Evaluating the optimal dose of teicoplanin with therapeutic drug monitoring: not too high for adverse event, not too low for treatment efficacy - Si-Ho Kim; Cheol-In Kang; Kyungmin Huh; Sun Young Cho; Doo Ryeon Chung; Soo-Youn Lee; Yae-Jean Kim; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Analysis of functional properties in the new Korean apple cultivar Arisoo - Young-Je Cho; Eun-Ho Lee; Jingi Yoo; Soon-Il Kwon; Hyong Woo Choi; In-Kyu Kang (Horticulture, Environment, and Biotechnology, 2019)

Paenibacillus lutimineralis sp. nov., Isolated From Bentonite - Eui-Sang Cho; In-Tae Cha; Dong-Ho Seo; Young-Do Nam; Seong Woon Roh; Jae-Hwan Kim; Myung-Ji Seo (Current Microbiology, 2019)

Inappropriate empirical antibiotic therapy does not adversely affect the clinical outcomes of patients with acute pyelonephritis caused by extended-spectrum β-lactamase-producing Enterobacteriales - Si-Ho Kim; Suhyun Oh; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Differential regional infarction, neuronal loss and gliosis in the gerbil cerebral hemisphere following 30 min of unilateral common carotid artery occlusion - Ji Hyeon Ahn; Minah Song; Hyunjung Kim; Tae-Kyeong Lee; Cheol Woo Park; Young Eun Park; Jae-Chul Lee; Jun Hwi Cho; Young-Myeong Kim; In Koo Hwang; Moo-Ho Won; Joon Ha Park (Metabolic Brain Disease, 2019)

Pathogenic significance of hemorrhagic pneumonia in hematologic malignancy patients with Stenotrophomonas maltophilia bacteremia: clinical and microbiological analysis - Si-Ho Kim; Min Kyeong Cha; Cheol-In Kang; Jae-Hoon Ko; Kyungmin Huh; Sun Young Cho; Doo Ryeon Chung; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Standardized Citrus unshiu peel extract ameliorates dexamethasone-induced neurotoxicity and depressive-like behaviors in mice - Dong Wook Lim; Min Young Um; Taewon Han; Jaekwang Lee; Yun Tai Kim; Suengmok Cho; In-Ho Kim; Daeseok Han; Changho Lee (Metabolic Brain Disease, 2018)

Effects of three-dimensional spheroid culture on equine mesenchymal stem cell plasticity - Mi Jeong Park; Jienny Lee; Jeong Su Byeon; Da-Un Jeong; Na-Yeon Gu; In-Soo Cho; Sang-Ho Cha (Veterinary Research Communications, 2018)

Inverse agonist of ERRγ reduces cannabinoid receptor type 1-mediated induction of fibrinogen synthesis in mice with a high-fat diet-intoxicated liver - Yaochen Zhang; Don-Kyu Kim; Yoon Seok Jung; Yong-Hoon Kim; Yong Soo Lee; Jina Kim; Won-IL Jeong; In-Kyu Lee; Sung Jin Cho; Steven Dooley; Chul-Ho Lee; Hueng-Sik Choi (Archives of Toxicology, 2018)

Brain ischemic preconditioning protects against moderate, not severe, transient global cerebral ischemic injury - Jae-Chul Lee; Bich-Na Shin; Jeong Hwi Cho; Tae-Kyeong Lee; In Hye Kim; YooHun Noh; Sung-Su Kim; Hyang-Ah Lee; Young-Myeong Kim; Hyeyoung Kim; Jun Hwi Cho; Joon Ha Park; et al. (Metabolic Brain Disease, 2018)

Neuronal loss and gliosis in the rat striatum subjected to 15 and 30 minutes of middle cerebral artery occlusion - Joon Ha Park; Jeong Hwi Cho; Ji Hyeon Ahn; Soo Young Choi; Tae-Kyeong Lee; Jae-Chul Lee; Bich Na Shin; Seongkweon Hong; Yong Hwan Jeon; Young-Myeong Kim; In Koo Hwang; Young Joo Lee; et al. (Metabolic Brain Disease, 2018)

Real Data Assimilation Using the Local Ensemble Transform Kalman Filter (LETKF) System for a Global Non-hydrostatic NWP model on the Cubed-sphere - Seoleun Shin; Jeon-Ho Kang; Hyoung-Wook Chun; Sihye Lee; Kwangjae Sung; Kyoungmi Cho; Youngsoon Jo; Jung-Eun Kim; In-Hyuk Kwon; Sujeong Lim; Ji-Sun Kang (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Effect of organic fertilizer application on growth characteristics and saponin content in Codonopsis lanceolata - Kyeong Gon Moon; In Seok Um; Seung Ho Jeon; Young Son Cho; Young-Guk Kim; Il Rae Rho (Horticulture, Environment, and Biotechnology, 2018)

Roles of HIF-1α, VEGF, and NF-κB in Ischemic Preconditioning-Mediated Neuroprotection of Hippocampal CA1 Pyramidal Neurons Against a Subsequent Transient Cerebral Ischemia - Jae-Chul Lee; Hyun-Jin Tae; In Hye Kim; Jeong Hwi Cho; Tae-Kyeong Lee; Joon Ha Park; Ji Hyeon Ahn; Soo Young Choi; Hui Chen Bai; Bich-Na Shin; Geum-Sil Cho; Dae Won Kim; et al. (Molecular Neurobiology, 2017)

Characterization of trichome morphology and aphid resistance in cultivated and wild species of potato - Kwang-Soo Cho; Min Kwon; Ji-Hong Cho; Ju-Sung Im; Young-Eun Park; Su-Young Hong; In-Taek Hwang; Jin-Ho Kang (Horticulture, Environment, and Biotechnology, 2017)

Urinary 6β-Hydroxycortisol/Cortisol Ratio Most Highly Correlates With Midazolam Clearance Under Hepatic CYP3A Inhibition and Induction in Females: A Pharmacometabolomics Approach - Kwang-Hee Shin; Li Young Ahn; Man Ho Choi; Ju-Yeon Moon; Jieon Lee; In-Jin Jang; Kyung-Sang Yu; Joo-Youn Cho (The AAPS Journal, 2016)

Effects of Chronic Scopolamine Treatment on Cognitive Impairments and Myelin Basic Protein Expression in the Mouse Hippocampus - Joon Ha Park; Hyun Young Choi; Jeong-Hwi Cho; In Hye Kim; Tae-Kyeong Lee; Jae-Chul Lee; Moo-Ho Won; Bai Hui Chen; Bich-Na Shin; Ji Hyeon Ahn; Hyun-Jin Tae; Jung Hoon Choi; et al. (Journal of Molecular Neuroscience, 2016)

Is there a relationship between PPARD T294C/PPARGC1A Gly482Ser variations and physical endurance performance in the Korean population? - Han-Jun Jin; In-Wook Hwang; Ki-Cheol Kim; Hyun-Ik Cho; Tae-Hwan Park; Yun-A Shin; Ho-Seong Lee; Ji-Hyun Hwang; Ah-Ram Kim; Kwang-Hee Lee; Ye-Eun Shin; Ji-Yeon Lee; et al. (Genes & Genomics, 2016)

Chondrogenic potential and anti-senescence effect of hypoxia on canine adipose mesenchymal stem cells - Jienny Lee; Jeong Su Byeon; Keum Sil Lee; Na-Yeon Gu; Gyeong Been Lee; Hee-Ryang Kim; In-Soo Cho; Sang-Ho Cha (Veterinary Research Communications, 2016)

MicroRNA sequencing detects miR-424-5p up-regulation in ovarian cancer stem cells - Ji Ho Yun; Jisun Lim; In Su Ha; Ji Min Shin; Jung Hoon Kim; Jungho Kim; Chu Won Nho; Yoon Shin Cho (Genes & Genomics, 2015)

Predisposing roles of paraoxonase-1 genetic variants in Korean ischemic stroke patients - Yunkyung Cho; Jung Oh Kim; Young Joo Jeon; Gun Ho Choi; Jee Soo Shin; Sung Hwan Cho; Seung Hun Oh; In Bo Han; Byoung Soo Shin; Ok Joon Kim; Nam Keun Kim (Genes & Genomics, 2015)

Phenolic components from Rhus parviflora fruits and their inhibitory effects on lipopolysaccharide-induced nitric oxide production in RAW 264.7 macrophages - Sabina Shrestha; Dae-Young Lee; Ji-Hae Park; Jin-Gyeong Cho; Dong-Sung Lee; Bin Li; Youn-Chul Kim; Geum-Soog Kim; Myun-Ho Bang; Nam-In Baek (Natural Product Research, 2013)

Treadmill exercise represses neuronal cell death and inflammation during Aβ-induced ER stress by regulating unfolded protein response in aged presenilin 2 mutant mice - Eun-Bum Kang; In-Su Kwon; Jung-Hoon Koo; Eung-Joon Kim; Chul-Hyun Kim; Jin Lee; Choon-Ho Yang; Young-Il Lee; In-Ho Cho; Joon-Yong Cho (Apoptosis, 2013)

The prevalence of BRCA mutations among familial breast cancer patients in Korea: results of the Korean Hereditary Breast Cancer study - Sang-Ah Han; Sung-Won Kim; Eunyoung Kang; Sue K. Park; Sei-Hyun Ahn; Min Hyuk Lee; Seok-Jin Nam; Wonshik Han; Young Tae Bae; Hyun-Ah Kim; Young Up Cho; Myung Chul Chang; et al. (Familial Cancer, 2013)

Capsaicin-induced apoptosis in the human glioblastoma U87MG cells via p-38 MAPK and Bcl-2/Bax signaling pathway - Jin Ho Jeon; Yoon Ji Choi; In Ho Han; Byung Kwan Choi; Seung Heon Cha; Won Ho Cho (Molecular & Cellular Toxicology, 2012)

QTL analysis of fruit length using rRAMP, WRKY, and AFLP markers in chili pepper - Heung-Ryul Lee; Ki-Taek Kim; Hyoun-Joung Kim; Jung-Heon Han; Jeong-Ho Kim; Seon-In Yeom; Hyun Jung Kim; Won-Hee Kang; Jinxia-Shi; Soung-Woo Park; Ik-Hyun Bae; Semin Lee; et al. (Horticulture, Environment, and Biotechnology, 2011)

Knockout of a starch synthase gene OsSSIIIa/Flo5 causes white-core floury endosperm in rice (Oryza sativa L.) - Nayeon Ryoo; Chul Yu; Cheon-Seok Park; Moo-Yeol Baik; In Myoung Park; Man-Ho Cho; Seong Hee Bhoo; Gynheung An; Tae-Ryong Hahn; Jong-Seong Jeon (Plant Cell Reports, 2007)

Reproducibility of Quantitative Estimate of Magnetocardiographic Ventricular Depolarization and Repolarization Parameters in Healthy Subjects and Patients with Coronary Artery Disease - Hyun Kyoon Lim; Namsik Chung; Kiwoong Kim; Young-Guk Ko; Hyukchan Kwon; Yong-Ho Lee; Jin-Bae Kim; Jung Rae Cho; Jin-Mok Kim; In-Seon Kim; Yong Ki Park (Annals of Biomedical Engineering, 2006)

In vivo MR Imaging of Tissue-engineered Human Mesenchymal Stem Cells Transplanted to Mouse: a Preliminary Study - In Kap Ko; Ho-Taek Song; Eun-Jin Cho; Eun Sook Lee; Yong-Min Huh; Jin-Suck Suh (Annals of Biomedical Engineering, 2006)

Production of Indole-3-Acetic Acid in the Plant-Beneficial Strain Pseudomonas chlororaphis O6 Is Negatively Regulated by the Global Sensor Kinase GacS - Beom Ryong Kang; Kwang Yeol Yang; Baik Ho Cho; Tae Ho Han; In Seon Kim; Myung Chul Lee; Anne J. Anderson; Young Cheol Kim (Current Microbiology, 2006)

Decolorization of triphenylmethane and azo dyes by Citrobacter sp. - Sun-Young An; Sang-Ki Min; In-Ho Cha; Yong-Lark Choi; Young-Su Cho; Cherol-Ho Kim; Young-Choon Lee (Biotechnology Letters, 2002)